Antimutagenicity of lemon grass (Cymbopogon citratus Stapf) to various known mutagens in salmonella mutation assay - Vinitketkumnuen U. (2014)
Lemon grass (Cymbopogon citratus Stapf) was extracted with 80% ethanol. The extract was not found to be mutagenic in the Salmonella mutation test with or without metabolic activation. However, the extract was found to possess antimutagenic properties towards chemical-induced mutation in Salmonella typhimurium strains TA98 and TA100. Mutagenicity of AFB1, Trp-P-1, Trp-P-2, Glu-P-1, Glu-P-2, IQ, MNNG and AF-2, was inhibited by the extract of lemon grass in a dose-dependent manner, but no effect was found on the mutagenic activity of benzo[a]pyrene.